SWOT Analysis in Determining Performance Improvement Strategies - Azandi Wilasto, Kukuh; Wening, Nur (Jurnal Ekuisci, 2025)
Background. This research was conducted to identify and systematically examine the application of the Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis in the formulation of strategies to enhance organizational performance across various sectors. Aims. The study's focus encompasses the fields of education, public services, industry, Micro, Small, and Medium Enterprises (MSMEs), and hospitals. Methods. The methodology employed in this study is a Systematic Literature Review (SLR) of ten scientific articles published between 2017 and 2024, which explicitly applies the SWOT approach. The study was conducted thematically, based on the research method, organizational sector, SWOT quadrant position, and proposed strategy. Result. The results of the study show that most organizations are in quadrant I (aggressive strategy), which describes an institution's ability to combine strengths from internal operations and opportunities from external sources to the maximum. The dominant strategy implemented includes strengthening human resources, implementing performance improvement strategies, enhancing operational process efficiency, and driving innovation in products and work systems. In addition, some studies combine SWOT with other methods such as the Quantitative Strategic Planning Matrix (QSPM) and the Malcolm Baldrige National Quality Award (MBNQA), which have been proven to enrich analysis and support decision-making accuracy. Conclusion. SWOT analysis has proven to be an effective strategic evaluation tool applicable in various organizational contexts. This study also offers practical implications for organizational leaders in designing adaptive strategies that are grounded in the organization's actual conditions. Implementation. The government and stakeholders are advised to initiate managerial training and mentoring programs to enhance organizational understanding and capacity in comprehensively implementing SWOT analysis